Effect of Acetazolamide Additional Therapy on Loop Diuretic for Achieving an Effective Treatment in Acute Heart Failure Patients: A Systematic Review - Annisa T. Fadilla; Muhammad Sabri; Idham Junantaruna; Ajibaskoro P. Ibrahim (Universitas Sam Ratulangi, 2024)
Abstract: Hospital readmissions are primarily caused by signs and symptoms of congestion of acute heart failure (AHF). Loop diuretics are commonly used to treat volume excess. It has been suggested by earlier studies in AHF patients that combination of loop diuretics with acetazolamide can increase the effectiveness of loop diuretics. This study aimed to obtain the impact of acetazolamide addition on loop diuretic therapy in AHF patients and assess the benefit of the combination. This was a systematic review using PubMed and ScienceDirect to retrieve data in 2013 and 2023, focusing on Randomized Controlled Trials (RCTs) involving AHF patients treated with both loop diuretics and acetazolamide. The results showed that 573 patients from a total of four RCTs were included in the study. Acetazolamide additional therapy helped loop diuretic to increase natriuresis (in all of the studies) and urine output (in two studies). The congestion symptoms also reduced in patients who received acetazolamide additional therapy on dose 500 mg intravenously within three days (p<0.05) in two studies. However, patients who received acetazolamide therapy also had an increase in serum creatinine levels in two studies. In conclusion, adding acetazolamide to loop diuretic therapy can increase the effectiveness of loop diuretics to achieve successful decongestion in AHF patients. Additionally, acetazolamide-treated individuals exhibit natriuresis and urin output higher than those in the control group, despite it also raises serum creatinin level. Keywords: acetazolamide; loop diuretics; acute heart failure; decongestion